2005
DOI: 10.1063/1.2058184
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet light-assisted domain inversion in magnesium-doped lithium niobate crystals

Abstract: Articles you may be interested inPyroelectric field assisted ion migration induced by ultraviolet laser irradiation and its impact on ferroelectric domain inversion in lithium niobate crystals Light-induced superlow electric field for domain reversal in near-stoichiometric magnesium-doped lithium niobateThe influence of ultraviolet ͑UV͒ light ͑wavelengths = 334 and 305 nm͒ on the ferroelectric domain inversion of lithium niobate crystals doped with different amounts of magnesium ranging from 0 to 7.5 mol % is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 35 publications
(25 reference statements)
3
27
0
2
Order By: Relevance
“…In comparison, our experimental conditions contained very high concentration of proteins and the sticky fibrinogen leads to a rapid formation of a proteinaceous overlayer that was found to be independent of the polarization. While the adsorption of molecules on polarized surfaces seems to be quite complex, the general notion that molecular interaction with the surfaces might depend on the fields present is supported by the observation that in the region of the ferroelectric domain boundaries the photo-reduction rate of AgNO 3 , HAuCl 4 , Pt (NO 3 ) 2 and other compunds is increased [23,[36][37][38][39]. In addition it was found that nanowires of pure Ag, Au and Pt were grown along the predefined 180 0 ferroelectric domain walls on c-cut congruent LiNbO 3 Less was so far known on interaction of cells with patterned, polarized substrates.…”
Section: Christophis Et Al Biointerphases 2013 8:27mentioning
confidence: 75%
“…In comparison, our experimental conditions contained very high concentration of proteins and the sticky fibrinogen leads to a rapid formation of a proteinaceous overlayer that was found to be independent of the polarization. While the adsorption of molecules on polarized surfaces seems to be quite complex, the general notion that molecular interaction with the surfaces might depend on the fields present is supported by the observation that in the region of the ferroelectric domain boundaries the photo-reduction rate of AgNO 3 , HAuCl 4 , Pt (NO 3 ) 2 and other compunds is increased [23,[36][37][38][39]. In addition it was found that nanowires of pure Ag, Au and Pt were grown along the predefined 180 0 ferroelectric domain walls on c-cut congruent LiNbO 3 Less was so far known on interaction of cells with patterned, polarized substrates.…”
Section: Christophis Et Al Biointerphases 2013 8:27mentioning
confidence: 75%
“…Standard masks can be made thinner yielding smaller structures. The similarity between UV illumination and ion exposure has been discovered before: both treatments yield a significant reduction of the coercive field E C [8,10,25], which implies that changes in the electronic structure of the material are crucial for the poling dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] In this paper, however, a different effect is presented whereby illumination of the +z face with UV light at = 244 nm ͑with photon energy greater than the LN band gap͒ inhibits domain inversion in illuminated areas during subsequent electric field poling ͑EFP͒. Of major importance, the inhibited domains are not restricted in their shape or alignment with the crystal x or y axes, hence, arbitrarily shaped domains can be formed.…”
mentioning
confidence: 99%